“Letting the ancestors speak”: collaborative archaeology at the Hastings Natural History Reservation - Sanchez, Gabriel M.; Apodaca, Alec; Gonzalez, Ariadna; Gonzalez, Carolina; Nason, Tom Little Bear; Herthel, Cari; Nason, Jana; Byram, Scott; Hunter, Jen (Frontiers in Environmental Archaeology, 2024)
Since 2021, collaborative research at the University of California (UC), Berkeley’s Hastings Natural History Reservation between the Esselen Tribe of Monterey County, UC-Berkeley, and the University of Oregon has demonstrated the mutual benefits of a co-created and Indigenous-centered archaeological research program within North America. While initial archaeological studies on the Hastings Reservation occurred over five decades ago, our project represents one of the first Tribal-centered archaeological field programs within the UC Natural Reserve System and, therefore, a model of collaborative research in the post-NAGPRA and CalNAGPRA era. The broader purpose of our research is to work with the Esselen Tribe to collect historical ecological information about the legacies of Native people and their relationship with the environment to help inform contemporary stewardship goals in their Tribal territory. Our archaeological research has confirmed the Indigenous occupation at the Hastings Reserve before, during, and after the Spanish Colonial period (1769 to 1821) in central California. By weaving archaeology, ethnobotany, ethnohistory, historical documents, ethnography, and Indigenous knowledge, this project documents the critical role of maintaining a connection to cultural landscapes despite three successive waves of European and Euro-American colonialism in the region. These findings provide an alternative narrative of cultural persistence, survivance, and resilience contrary to the narratives of culture loss and erasure espoused by 20th-century California anthropology regarding the Indigenous societies that occupied the central California coast.